Pengetahuan dan perilaku ramah lingkungan mahasiswa - Fubani, Amalia; Diheim, Muhammad; Makhya, Nadia; Velasufah, Whasfi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Human lifestyle behaviors today still pose environmental problems, including waste accumulation leading to pollution of water sources consumed by humans, resulting in a health crisis. One strategy that needs to be undertaken is a change in community behavior towards cleaner and more efficient consumption patterns. However, significant impacts on consumption patterns will not be significant if only one or two individuals do so. Good cooperation and sufficient knowledge are required to form collective awareness in environmentally friendly behavior. In relation to this, this scientific work examines the correlation between environmentally friendly behavior of Environmental Science students and income, age, gender, and educational background of SIL UI students. This research was conducted by surveying 47 students of the Environmental Science School UI batch 40A. The results of this study show that income has a slight correlation with the four dimensions of environmentally friendly behavior: recycling, transportation & mobility, energy conservation, and environmentally friendly consumption.